KAJIAN EKSTRAK TUNAS BAMBU DAN TAUGE TERHADAP PERTUMBUHAN TANAMAN KELAPA SAWIT (Elaeis guineensis Jacq.) PADA PEMBIBITAN PRE NURSERY - Asritanarni Munar; Azharuddin Lubis; Abdullah Yaksan; Ade Ryantika; Khairunnas ,; Juwita Tarigan (UNIVERSITAS MUHAMMADIYAH SUMATERA UTARA, 2011)
AbstractResearch was conducted using a randomized block design (RBD), non-factorial with 10 treatments and 3 replications and tested using Duncant Multiple Range Test (DMRT) to see the effect of extract of bamboo shoots and bean sprouts on the growth of oil palm seedlings in pre nursery with five measurement parameters namely plant height (cm), number of leaves (leaves), leaf area (cm2), seedling dry weight (grams) and seedling fresh weight (grams). In this study differences in the doses used in the treatment level is too low at 0.5 cc / l. So the difference of the data obtained is not significant between all treatment levels. But from the results of the study dose of 1 cc / l in the use of bamboo shoot extract is more effective for high growth, leaf number, leaf area, fresh weight and dry weight of oil palm seedlings, and in the use of effective sprouts extract on the growth of plant height and leaf area.Keywords: palm oil, ZPT, bamboo shoots. bean sprouts.